2021
DOI: 10.1002/maco.202112347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of steel corrosion in alkaline sulfate solution by electrochemical noise

Abstract: Research on the effects of sulfate ions on steel corrosion has been conducted in response to the observations of premature localized corrosion of steel strands in cementitious grouts in posttensioned bridge construction. Electrochemical noise (EN) was shown to be an effective technique to assess the development of localized corrosion of steel in the alkaline sulfate solution.General statistics of the EN potential and current time signatures revealed the negative effect of elevated sulfate concentrations and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The spacer was also used to secure a microsaturated silver/silver‐chloride (Ag/AgCl) reference electrode. Details of the test setup can be found in Permeh et al [ 29 ] All test cells were assembled with sterile components and the test specimens were rinsed in deionized water and sterilized with ethanol solution before testing. The test cells were filled with 200 ml of solution collected from a natural water test site in Miami, Florida.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spacer was also used to secure a microsaturated silver/silver‐chloride (Ag/AgCl) reference electrode. Details of the test setup can be found in Permeh et al [ 29 ] All test cells were assembled with sterile components and the test specimens were rinsed in deionized water and sterilized with ethanol solution before testing. The test cells were filled with 200 ml of solution collected from a natural water test site in Miami, Florida.…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical noise (EN) technique has been shown to differentiate corrosion modality. [24][25][26][27][28][29] Comparisons of the spontaneous transient noise current and potential signature, statistical analysis of noise in the time domain, power-spectral density (PSD), and shot noise analysis have been used to identify the development of localized corrosion. [24,30] Of particular interest to identify MIC, EN can ideally identify pitting corrosion [31][32][33][34][35] and other heterogeneities associated with reactions under biofilms.…”
mentioning
confidence: 99%
“…The electrochemical noise (EN) technique has several advantages that may be leveraged for corrosion monitoring. [28][29][30][31][32] The use of electrochemical techniques including EN to identify carbonation-induced corrosion is explored.…”
Section: Co + Ca(oh)mentioning
confidence: 99%
“…Due to the corrosion tendon failures in a Florida bridge in 2011 [8] associated with a prepackaged thixotropic grout that had developed material segregation, it was of interest to identify corrosion testing methods that would account for the susceptibility of grout materials to form physical and chemical deficiencies. It would be suggested that testing attuned to grout segregation (such as to identify grout robustness and corrosion mitigation) could be used to prescribe grouts resistant to aberrations in construction and provide greater confidence in material selection [38][39][40][41]. Full scale tendon mockups such as those required prior to bridge construction in Virginia for grout material selection may be cost prohibitive and excessive.…”
Section: Introductionmentioning
confidence: 99%